Total antioxidant capacity, total oxidant level and oxidative stress index in patients with laryngopharyngeal reflux with Helicobacter pylori IGG positivity - Mutlu, Önder; Kar, Murat; Yıldız Zeyrek, Fadile; Aksoy, Nurten; Taşkın, Abdullah (ENT Updates, 2013)
Objective: The aim of this study is to investigated the relationship between H. pylori IgG positivity, total antioxidant capacity (TAC), total oxidant level (TOL) and oxidative stress index (OSI) in patients with laryngopharyngeal reflux (LPR). Methods: A total of 48 patients with laryngopharyngeal reflux (LPR) were included into the study group. Of these patients, 20 with H. pylori IgG (-), LPR (+) were included into Group 2; and 28 patients with H. pylori IgG (+), LPR (+) were included into Group 3. The control group (Group 1) consisted of 19 healthy subjects. In all groups, total antioxidant capacity, total oxidant level and oxidative stress index were studied. Results: Group 3's total oxidant level values were significantly higher than those of Group 1 (p=0.000) and Group 2 (p=0.000); and Group 2's total oxidant level values were significantly higher than Group 1. Group 3's oxidative stress index values were significantly higher than those of Group 1 (p=0.000) and Group 2 (p=0.000), and Group 2's oxidative stress index values were significantly higher than Group 1 (p=0.001). Conclusion: The presence of LFR alone, or LFR and increase in the level of serum IgG antibody developed against H. pylori, lead to increase in total oxidant level and oxidative stress index. Both LPR and to be infected with H. pylori and development of H. pylori IgG antibodies lead to an increase in total oxidant level and oxidative stress index; and an increase in free radicals ultimately lead to an increase in oxidative stress in the body.